2001
DOI: 10.1007/s004150170140
|View full text |Cite
|
Sign up to set email alerts
|

The course of the terminal phase in patients with amyotrophic lateral sclerosis

Abstract: The fear of "choking to death" is on the mind of most patients suffering from amyotrophic lateral sclerosis (ALS). So far, however, there have been no systematic surveys concerning the dying phase in a general ALS population. We therefore performed a structured telephone interview with the relatives of 121 patients who died from ALS and were followed by the Motor Neuron Outpatient Clinic of the Department of Neurology, University of Munich, Germany. These data are compared with those obtained by a retrospectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
109
2
6

Year Published

2002
2002
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 207 publications
(118 citation statements)
references
References 23 publications
1
109
2
6
Order By: Relevance
“…Interestingly, the amyotrophic lateral sclerosis functional rating scale (ALSFRS), a disease-specific rating scale that assesses functional impairment, has been shown to predict both length of hospital stay as a result of acute respiratory failure and survival after initiation of invasive ventilation in these patients (Lo Coco et al, 2007). Notwithstanding its effect on survival, only a minority of patients with ALS receive invasive mechanical ventilation, at least in the western Countries (Moss et al, 1993;Miller et al, 2000;Neudert et al, 2001). On the contrary, in Japan the frequency of invasive ventilation is considerably higher.…”
Section: Invasive Mechanical Ventilationmentioning
confidence: 99%
“…Interestingly, the amyotrophic lateral sclerosis functional rating scale (ALSFRS), a disease-specific rating scale that assesses functional impairment, has been shown to predict both length of hospital stay as a result of acute respiratory failure and survival after initiation of invasive ventilation in these patients (Lo Coco et al, 2007). Notwithstanding its effect on survival, only a minority of patients with ALS receive invasive mechanical ventilation, at least in the western Countries (Moss et al, 1993;Miller et al, 2000;Neudert et al, 2001). On the contrary, in Japan the frequency of invasive ventilation is considerably higher.…”
Section: Invasive Mechanical Ventilationmentioning
confidence: 99%
“…There is now evidence that, with good palliative care, death is not distressing and most often it is peaceful (Neudert et al 2001).…”
Section: Fears Of Dyingmentioning
confidence: 99%
“…The deterioration of a patient with MND is variable. Patients usually deteriorate slowly and it gradually becomes apparent that the disease has reached the terminal stage, but for many patients the changes are rapid, over a few days (Neudert et al 2001). One study showed that for 65% of patients the period between the acute deterioration and death was under 24 h (Neudert et al 2001).…”
Section: The Terminal Stagesmentioning
confidence: 99%
See 2 more Smart Citations